The fortuna of Peter I of Castile’s "Trojan History" (BMP ms. 558). Notes about its genesis, provenance and vicissitudes - Pichel Gotérrez, Ricardo (Madrygal. Revista de Estudios Gallegos, 2012)
This article presents some aspects related to the genesis, the origin and the external history of ms. 558 Menendez Pelayo Library, known as the Trojan History “bilingual” (XIVth) by combining independently Castilian and Galician in the final drafting. This is a manuscript originally written in Castilian commissioned by the king Peter I of Castile in the late sixties, that, after a significant deterioration, would be restored and completed in Galician a little bit later (ca. 1369-1371), under the auspices of Nuno Freire de Andrade, Master of the Portuguese Order of Christ. The socio-political and cultural context that conditioned the genesis of this work (both in its primitive Castilian version as in its hybrid Galician-Castilian drafting that we have preserved till today), along with the vicissitudes through which the manuscript passed from late Middle Age till its incorporation into the valuable documentary collection of Mr. Marcelino Menéndez Pelayo in the late XIX, will be the main points of discussion in this research.
Keywords: medieval literature and history; Peter I of Castile; Nuno Freire de Andrade; House of Lemos; House of Astorga-Altamira; Marcelino Menéndez Pelayo.